Parental Perspectives towards the Vocational Education Training Sector in Vietnam - Dang, Vi Hoang (Journal of Education and Vocational Research, 2015)
The main purpose of this study is to explore the parental perspectives of the vocational education and training (VET) sector in Vietnam. The data were collected from 32 parents in the Northern and Southern regions using six open-ended interview questions focussing on the vocational education training system. Several techniques, namely word repetitions, keywords in context, and similarities and differences were applied to discover the common emerging themes and sub-themes. The issues which corresponded with the six questions were (1) quality and types of VET input, (2) VET teachers’ ability, (3) facilities and equipment, (4) the relationship between VET providers and industries, (5) recognition of VET qualifications and (6) job potential. The results indicated two main positive and negative themes emerging in five of the issues, the exception being the relationship between VET providers and industries. The issue of job potential was evaluated positively by parents. However, the findings indicate wastage of trained manpower due to the weak relationship between VET providers and industries. The recommendations are that Government agencies should be more involved in the VET sector by providing teaching protocols and implementing policy concerning two-way collaboration between VET providers and enterprises, making the sector more attractive to parents, students, industries and other key stakeholders with the primary aim of changing perceptions of the VET sector positively.